The Relationship Between the Level of Knowledge and Patterns of Use of Traditional Medicine As Self-Medication on Health Maintenance in the Kelurahan Cawang, East Jakarta - Silaban, Hertina; Utomo, Tranggono Yudo; Pangestika, Vania (CV. AFDIFAL MAJU BERKAH, 2025)
Many Indonesians use traditional medicine to maintain their health status. Self-medication is a common practice that many people do to overcome minor health problems before seeking professional medical help. The purpose of this study was to determine how well the residents of RW 11 Kelurahan Cawang East Jakarta know about traditional medicine and how to use it to maintain health. The research method was a cross-sectional questionnaire survey with an observational analytic design. In this study, a total of 147 participants were selected using a selective selection strategy, which is not a random sampling procedure. According to the data collected, most of the respondents were male (55.1%), the highest age range was 50-59 years old (33.3%), and the education level was high school (59.9%). The results showed that 76.2% (112 people) had a good level of knowledge in the use of traditional medicine. The majority of Cawang people have used traditional medicine as self-medication, classified as a good group of 78.9% (116 people). To maintain health in the use of traditional medicine is classified as a good group of 59.9% (88 people). The linear graph also shows there is a linear relationship between the extent of the Cawang community's knowledge of traditional medicine and the frequency with which they use it as self-medication to maintain health. There needs to be more emphasis on educating the community about the benefits of traditional medicine and how to use it safely and effectively.